2017
DOI: 10.1002/jobm.201700275
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprofile and functional diversity of fungal and bacterial endophytes and role of ecofactors - A review

Abstract: Endophytes represent a hidden world within plants. Almost all plants that are studied harbor one or more endophytes, which help their host to survive against pathogens and changing adverse environmental conditions. Fungal and bacterial endophytes with distinct ecological niches show important biological activities and ecological functions. Their unique physiological and biochemical characteristics lead to the production of niche specific secondary metabolites that may have pharmacological potential. Identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Dothidiomycetes, Sordariomycetes, Leotiomycetes and Eurotiomycetes belonging to the phylum Ascomycota were both found in five plant species in this study, Yao et al [35] found endophytic and epiphytic were dominated by Dothideomycetes and Tremellomycetes in a tropical mangrove ecosystem. Some members, like Alternaria , Aspergillus , Penicillium , Fusarium , are considered as endophytes supported by various investigations [36,37], which were both detected in the five plant species of this study. This phenomenon further emphasizes that there is an overlap between epiphytic and endophytic fungal communities [38].…”
Section: Discussionsupporting
confidence: 80%
“…Dothidiomycetes, Sordariomycetes, Leotiomycetes and Eurotiomycetes belonging to the phylum Ascomycota were both found in five plant species in this study, Yao et al [35] found endophytic and epiphytic were dominated by Dothideomycetes and Tremellomycetes in a tropical mangrove ecosystem. Some members, like Alternaria , Aspergillus , Penicillium , Fusarium , are considered as endophytes supported by various investigations [36,37], which were both detected in the five plant species of this study. This phenomenon further emphasizes that there is an overlap between epiphytic and endophytic fungal communities [38].…”
Section: Discussionsupporting
confidence: 80%
“…The infection by PVY results in a wide range of symptoms, such as vein necrosis and systematic mottles, with necrotic ringspots reducing crop yield and quality substantially (Chen et al, 2017 ). Upon infection, plants activate their defense mechanisms by producing various resistant substances, including phytoalexin chitinase, peroxidase, and plant antitoxin to enhance their tolerance (Shah et al, 2017 ). Furthermore, the presence of PVY in a host organism leads to the observation of numerous morphological, physiological, and histological alterations (Hinrichs-Berger et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the exploration of the complex biosynthesis of the metabolites of medicinal plants with their endophytic microorganisms has been insufficiently investigated. Endophytic fungi are an essential biotechnological source because they can be involved in the production of a pharmacologically active and structurally diverse range of secondary metabolites together with the host plant and might even be the sole producer [ 15 , 16 , 17 ]. Numerous bioactive natural compounds with antimicrobial [ 18 , 19 ], anti-inflammatory [ 20 ], cytotoxic [ 21 , 22 ], antioxidant [ 23 ], antidiabetic [ 24 ] and acetylcholinesterase [ 25 ] inhibitory activity have been isolated from endophytic fungi.…”
Section: Introductionmentioning
confidence: 99%